2017
DOI: 10.1177/1933719116681517
|View full text |Cite
|
Sign up to set email alerts
|

Smad3/4 Binding to Promoter II of P450arom So As to Regulate Aromatase Expression in Endometriosis

Abstract: Activin A can stimulate aromatase P450 (P450arom) expression in eutopic endometrial stromal cells (ESCs) of endometriosis by activin type I receptor-Smad pathway. In order to identify Smad3/4 binding to P450arom promoter II that mediates activin A response in ESCs, polymerase chain reaction (PCR) products of a serial truncated deletion of the P450arom promoter II region between -904 and +87 bp were inserted into the pGL3-basic vector to generate the promoter reporter plasmids. Luciferase reporter plasmids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Endometriosis is a benign disease going through tumor-like processes to form endometriotic lesions. Tumor-like processes include aggression, 5 evasion [epithelial-mesenchymal transition (EMT)], 6,7 adhesion (CD10 and integrins), 8 invasion (matrix metalloproteinases), 9 angiogenesis (vascular endothelial growth factor), 10,11 surviving (hormones and aromatase), 12 fibroproliferation, 13 and inflammation (cytokines). 14,15 Although these mechanisms have been studied for a long time, more research is still needed as the current medical therapies have many adverse effects and are not plausible because of the high recurrence rate after performing conservative surgery.…”
mentioning
confidence: 99%
“…Endometriosis is a benign disease going through tumor-like processes to form endometriotic lesions. Tumor-like processes include aggression, 5 evasion [epithelial-mesenchymal transition (EMT)], 6,7 adhesion (CD10 and integrins), 8 invasion (matrix metalloproteinases), 9 angiogenesis (vascular endothelial growth factor), 10,11 surviving (hormones and aromatase), 12 fibroproliferation, 13 and inflammation (cytokines). 14,15 Although these mechanisms have been studied for a long time, more research is still needed as the current medical therapies have many adverse effects and are not plausible because of the high recurrence rate after performing conservative surgery.…”
mentioning
confidence: 99%
“…The result of 4.5 fold increase in estrogen production in endometriotic stromal cells stimulated with activated platelets vs. those unstimulated is remarkably close to the reported fold increase found between testosterone-added endometriotic and endometrial stromal cells (4.1 for follicular phase and 4.5 for luteal phase) 41 . Previous studies have reported that the TGF-β1/Smad3 signaling pathway is involved in the transcriptional regulation of aromatase in several cell types [56][57][58] , and particularly in endometriotic stromal cells 59 . www.nature.com/scientificreports www.nature.com/scientificreports/ Therefore, our finding is also consistent with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, persistently low levels of IkBα immunoreactivity in ectopic endometrial cells are likely to be related to the increased local inflammation observed in endometriosis and may contribute to the increased inflammatory cytokine levels in the peritoneal cavity of women with endometriosis ( 60 , 61 ) . Endometriosis is an estrogen-dependent disease and implants of endometriosis have sufficient enzymes for the local production of estrogen ( 54 , 59 , 62 , 63 , 64 ) . The low levels of IkBα in ectopic endometrial cells suggest that the signaling effects of estrogen on IkBα may function similarly to those observed in eutopic endometrium.…”
Section: Discussionmentioning
confidence: 99%